Estimating the need for palliative care at the population level: A cross-national study in 12 countries. (June 2017) - Morin, Lucas; Aubry, Régis; Frova, Luisa; MacLeod, Roderick; Wilson, Donna M; Loucka, Martin; Csikos, Agnes; Ruiz-Ramos, Miguel; Cardenas-Turanzas, Marylou; Rhee, YongJoo; Teno, Joan; Öhlén, Joakim; et al.
Background: To implement the appropriate services and develop adequate interventions, detailed estimates of the needs for palliative care in the population are needed. Aim: To estimate the proportion of decedents potentially in need of palliative care across 12 European and non-European countries. Design: This is a cross-sectional study using death certificate data. Setting/participants: All adults (⩾18 years) who died in 2008 in Belgium, Czech Republic, France, Hungary, Italy, Spain (Andalusia, 2010), Sweden, Canada, the United States (2007), Korea, Mexico, and New Zealand ( N  = 4, 908, 114). Underlying causes of death were used to apply three estimation methods developed by Rosenwax et al., the French National Observatory on End-of-Life Care, and Murtagh et al., respectively. Results: The proportion of individuals who died from diseases that indicate palliative care needs at the end of life ranged from 38% to 74%. We found important cross-country variation: the population potentially in need of palliative care was lower in Mexico (24%–58%) than in the United States (41%–76%) and varied from 31%–83% in Hungary to 42%–79% in Spain. Irrespective of the estimation methods, female sex and higher age were independently associated with the likelihood of being in need of palliative care near the end of life. Home and nursing home were the two places of deaths with the highest prevalence of palliative care needs. Conclusion: These estimations of the size of the population potentially in need of palliative care provide robust indications of the challenge countries are facing if they want to seriously address palliative care needs at the population level.